Penerapan Model Information Retrieval Untuk Pencarian Konten Pada Perpustakaan Digital - Fitriani, Eka; Indrajit, Richardus Eko; Aryanti, Riska (www.bsi.ac.id, 2017)
Digital library is the source of user information for library data search. The growing technology makes it easier for users to get the information they need. Digital libraries have a lot of content that causes search difficulties based on the interests of users. Using the N-Gram Method and Spelling Correction index applied to the search program will allow users to find the information they need, especially interest-based searches. This search process utilizes text information stored in digital library documents. In text documents, information is obtained directly from the content of the intended document. Keywords: Digital Library, information retrieval, N-Gram, Spelling Correction.